Leadership Style in Madrasah Aliyah: A Human-Oriented Leadership Practice (Gaya Kepemimpinan di Madrasah Aliyah: Suatu Praktik Kepemimpinan Berorientasi Manusia) - Rizmi Rahmawati (Shautut Tarbiyah, 2023)
This article aims to examine and analyze the leadership style of the madrasa principal in developing madrasas. The object of this research is the Head of Madrasah, Teachers, Chair of the MA Al-Mu'minin Ladongi Committee and Head of Educational Services at the Ministry of Religion of East Kolaka Regency. This research use desciptive qualitative approach. Data collection techniques were carried out by observation, interviews and documentation. Data analysis through the process of data reduction, presentation of data and drawing conclusions as well as checking the validity of data techniques through triangulation of techniques, sources and time. Based on the results of the study, it shows that 1) The way the madrasa head accepts criticism, opinions and suggestions from subordinates is through meeting activities that are held as a forum to receive input from his subordinates. 2) The way the head of the madrasa in the decision-making process is through meetings so that all subordinates are involved. 3) The way the head of the madrasa in creating a family atmosphere is by considering his subordinates as his own children and fellow teachers consider brothers and other teachers. With these things, the leadership style of the madrasa principal tends to be democratic.Keywords: Leadership Style, Madrasah Development